COMPARISON BETWEEN THE RELATIVISTIC AND NON-RELATIVISTIC TREATMENT OF THE Λ-HYPERNUCLEI - Koutroulos, C. G. (HNPS Advances in Nuclear Physics, 2020)
Using as an example potentials of the form U±(r)=-D±(cosh^2(r/R))^-1 the binding energies as well as the root mean square radii of the orbits of the Λ particle in hypernuclei in the ground and excited states were calculated in the relativistic and non-relativistic cases and the results are compared.